Optimalisasi GeoGebra Berdiferensiasi dalam Problem Based Learning untuk Pembelajaran Grafik Fungsi Kuadrat - Kolimo, Jefrianus (Jurnal Didaktika Pendidikan Dasar, 2025)
Mathematics is a very systematic and abstract subject. Quadratic function graph is one of the Basic Competencies (BC) that is very systematic with an abstract concept. This BC is systematic because there are many other supporting BCs and is stated as abstract because the concept being studied does not directly exist in students’ lives. Referring to this problem, in several experiences and observations that have been carried out, it was found that students did not understand the material on quadratic function graphs which affected student learning outcomes. In addition, the condition of students with various backgrounds in the class is another challenge in learning so far. This research is a Classroom Action Research (CAR) which is conducted to improve student learning outcomes by using Differentiated Geogebra media which is elaborated in the Problem Based Learning model. The problem presented in the PBL model is local culture in Sabu Raijua. Observation and test techniques are used for data collection. Furthermore, the data is analyzed using descriptive-quantitative methods. The results of this study are through differentiated Geogebra media elaborated with the PBL model in cycle I, the percentage of classical learning completion of the class is 56.25%. In cycle II, the completion of learning outcomes increased to 78.13%. The conclusion is that the use of differentiated geogebra media in the PBL model can improve student learning outcomes on the material of quadratic function graphs.